Seaweeds in Two Oceans: Beta-Diversity - Smit, Albertus J.; Bolton, John J.; Anderson, Robert J. (Frontiers in Marine Science, 2017)
Several species assembly mechanisms have been proposed to structure ecological communities. We assess the biogeography of seaweeds along 2,700 km of South Africa's coastline in relation to a thermal gradient produced by the Agulhas Current, and contrast this with the environmental structure created by the Benguela Current. We subdivided the coastline into `bioregions' to examine the regional patterning. To investigate the assembly mechanisms, we decomposed Sørensen's Beta-diversity into `turnover' (Bsim) and `nestedness-resultant' (Bsne) dissimilarities, and used distance-based redundancy analysis (db-RDA) to relate them to the Euclidian thermal difference, dE, and geographical distance. Moran's eigenvector maps (MEM) were used as an additional set of spatial constraints. Variation partitioning was then used to find the relative strengths of thermal and spatially-structured thermal drivers. Spatial and environmental predictors explained 97.9% of the total variation in Bsim and the thermal gradient accounted for 84.2% of this combined pool. Bsim was the major component of overall Beta-diversity in the Agulhas Current region, suggesting niche influences (environmental sorting) as dominant assembly process there. The much weaker thermal gradient in the Benguela Current-influenced region resulted in a high amount of Bsne that could indicate neutral assembly processes. The intensification of upwelling during the mid-Pliocene 4.6–3.2 Ma (i.e. historical factors) were likely responsible for setting up the strong disjunction between the species-poor west coast and species-rich south and east coast floras, and this separation continues to maintain two systems of community structuring mechanisms in the Atlantic and Indian Ocean influenced sides of South Africa.